From Compliance to Fatigue? Assessing the Effectiveness of ETLE in Indonesia’s Traffic Law Enforcement - Muhammad Ali Shahab; Riska Sri Handayani; Muhamad Erza Aminanto (Transpublika Publisher, 2025)
This study evaluates the effectiveness of Electronic Traffic Law Enforcement (ETLE) in Indonesia from 2019 to 2024, focusing on its role in increasing compliance within the framework of Deterrence Theory. Drawing on violation data from 12 urban jurisdictions (including Jakarta, Surabaya, and Denpasar) where ETLE has been implemented, the findings indicate that the system enhances the certainty of punishment, particularly in detecting administrative violations such as helmet infractions and missing documentation. However, its long-term effectiveness remains inconsistent, as fluctuations in violations suggest behavioral adaptation and deterrence fatigue. While ETLE initially led to a surge in detected violations, compliance declined in later years due to uneven enforcement between urban and rural areas, as well as limitations in addressing behavioral infractions such as reckless and distracted driving. These findings primarily reflect urban contexts, highlighting a need for broader geographic inclusion in future evaluations to ensure national applicability. The study suggests that certainty alone is insufficient for sustained deterrence without complementary measures such as effective penalty enforcement, geographic expansion, and public awareness campaigns. To maximize its impact, ETLE must be integrated with traditional law enforcement methods and adaptive policy strategies to ensure lasting compliance. Future research should assess ETLE’s direct influence on accident rates and long-term driver behavior, with particular attention to expanding the geographic scope to improve national representativeness and policy relevance.